Design and Experimental Study on the Storage Type Insulation Box with Multi-temperature - Xu Xiaofeng; Zhang Xuelai; Zhou Sunxi; Wang Yinghui; Liu Lu; Liu Sheng (Zhileng xuebao)
Truck logistics (LTL) receives much attention in cold-chain transportation logistics. To improve the economy of logistics and ensure the quality of the refrigerated transport of fruits and vegetables, two types of multi-temperature-zoned refrigerated incubators were designed. 87% C8H16O2 (n-octanoic acid) + 13% C14H28O2 (myristic acid) and H2O + 0.03 g/ml C6H7KO2 (potassium sorbate) were selected as cold storage and heat preservation materials. The experimental results show that the phase transition temperatures, latent heat and thermal conductivity of the two phase-change materials were 7.1 °C and 2.5 °C, 146.1 J/g and 256.2 J/g, 0.2832 W/(m?K) and 0.9427 W/(m?K), respectively. Additionally, the two phase-change materials showed excellent stability from the point of view of thermophysical properties under 100 freezing/melting cycles. Combined with vacuum insulation technology, the temperature test system of the heat preservation box in the multiple temperature zones was established by using the verification equipment of the product supply specification (good supply practice, GSP). The test results show that the large multi-temperature-zoned refrigerated incubator can maintain the temperature at 7–9 °C for approximately 13 h in Zone 2, and at ?2 to 0 °C for approximately 14 h in Zone 3. The small multi-temperature-zoned cold storage box can maintain the temperature at 7–8 °C for approximately 19 h in Zone 1, and at 0 °C for approximately 16 h in Zone 2.